Women and politics in democratic transitions: the case of Bhutan. Issue 2 (3rd April 2017) - Chuki, Sonam; Turner, Mark
Abstract : This article addresses the question of what happens to women in democratic transitions. Of particular concern is whether women are encouraged to participate in politics and to stand as candidates for seats in national legislatures. In many instances, women have made only marginal progress in seeking election and getting elected in newly democratized regimes. This situation has been the experience of Bhutan, a country that held its first national elections only in 2007–2008. Despite women making significant gains in areas such as education, health and employment in Bhutan and guarantees of gender equality in the Constitution, they have made a poor showing in electoral politics. The article uses the explanatory framework of patriarchy to explore women's minor participation in electoral politics. Of special concern are deeply rooted traditional concepts that have been employed today to exclude women from competing for and winning political office. The article concludes that because patriarchal attitudes are so deeply embedded only incremental progress will be made under current electoral rules. Alternatively, there could be quota systems as in some other South Asian countries.